Life cycle management of agricultural and animal wastes through integrated energy systems for a particular region - Şişman, Figen. (Thesis (Ph.D.)-Bogazici University. Institute of Environmental Sciences, 2011., 2011)
Life cycle management is very essential to sustainable development which aims a balance between environmental, social and economic dimensions over products’ life cycle. Life cycle management consists of methods to quantify and compare the environmental, social and economical analysis of providing goods and services. While Life Cycle Assessment (LCA) is used for estimating the potential environmental impacts of a product; Life Cycle Costing, LCC, is used to assess the total cost of that product during its life cycle. In this study, GaBi4 software is used as the LCA & LCC tool and EDIP 2003 is used as the LCA methodology. The proposed thesis has been prepared as an application of life cycle management to succeed integrated waste minimization and energy conservation for a specific region in Turkey. The thesis covers the environmental and economical evaluation of a pilot scale anaerobic digestion (AD) and biogas recovery system which has been built in Kocaeli, Turkey. The waste recipe which is utilized for biogas production consists of cattle manures, poultry manures, slaughterhouse wastes, vegetable wastes and grass as raw material. The environmental evaluation is made according to the category indicators which are global warming, acidification, aquatic eutrophication, terrestrial eutrophication, photochemical ozone formation (impact on vegetation), stratospheric ozone depletion and the results are compared with six other scenarios including AD of only cattle manure, fossil fuel resources (coal power plant (PP), natural gas PP) and other renewable energy sources (hydro PP, wind PP, Integrated gasification combined cycle (IGCC)). With a different point of view, these energy production scenarios were evaluated in broad system boundaries and it is determined with this study that if the animal and agricultural wastes are not utilised in anaerobic digestion and biogas recovery system, even the renewable energy systems will be less environmentally friendly. It is determined that only an integrated interpretation of the scenarios can conclude the potential environmental impacts.
Keywords: Manure gases -- Environmental aspects.; Animal waste -- Management.; Animal waste -- Environmental aspects.; Agricultural wastes -- Management.